Propuesta de localización óptima para relleno sanitario de contingencia para Sopó, Cundinamarca (2023)
This research is a study focused on the determination of an optimal site for an emergency or contingency landfill within Sopó, which aim is proposing an update to its fundamental landuse plan of the current politics administration. The research employs a methodological framework comprising a sequenced approach with the following key steps: 1. The definition of pertinent variables, criteria, and their respective weightings; 2. A multi-criteria assessment, utilizing the Analytic Hierarchy Process (AHP) methodology; 3. The establishment of location constraints for potential areas; 4. The execution of geoprocessing procedures using geographic information system software.